2019
DOI: 10.3390/ijms20164055
|View full text |Cite
|
Sign up to set email alerts
|

Glucose Restriction Plus Refeeding in Vitro Induce Changes of the Human Adipocyte Secretome with an Impact on Complement Factors and Cathepsins

Abstract: Adipose tissue is a major endocrine organ capable of secreting adipokines with a role in whole-body metabolism. Changes in the secretome profile during the development of obesity is suspected to contribute to the risk of health complications such as those associated with weight regain after weight loss. However, the number of studies on weight regain is limited and secretome changes during weight regain have hardly been investigated. In an attempt to generate leads for in vivo studies, we have subjected human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 78 publications
1
10
0
Order By: Relevance
“…A separate piece of muscle underwent a trypsin digestion protocol as previously described (Qiao et al, 2019) to cleave peptides. The peptide mixture was loaded onto an LC-MS/MS, configured as described previously (Qiao et al, 2019;Vogel et al, 2019).…”
Section: Liquid Chromatography-mass Spectrometry Analysismentioning
confidence: 99%
“…A separate piece of muscle underwent a trypsin digestion protocol as previously described (Qiao et al, 2019) to cleave peptides. The peptide mixture was loaded onto an LC-MS/MS, configured as described previously (Qiao et al, 2019;Vogel et al, 2019).…”
Section: Liquid Chromatography-mass Spectrometry Analysismentioning
confidence: 99%
“…Carbamidomethylation of cysteines was set as fixed modifications. Label free quantitation was conducted using the Minora Feature Detector node in the processing step and the Feature Mapper node combined with the Precursor Ions Quantifier node in the consensus step with default settings within Proteome Discoverer 2.2 ( Qiao et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…One method is to replace a serum-enriched or differentiating medium with a medium devoid of glucose, insulin and serum [27]. This method does not allow for the examination of the proteins secreted during the earlier stages of the cell culture process.…”
Section: Difficulties In Studying the Secretomementioning
confidence: 99%
“…In a study by Qiao et al [27], which was conducted using a peptide tagging method, 1326 proteins were identified, of which 230 were recognized by Deeploc as adipocytesecreted proteins. Signal IP detected the presence of a signal peptide in 328 proteins.…”
Section: Syndrome (Sgbs) Cellsmentioning
confidence: 99%
See 1 more Smart Citation